New DNA Methylation Markers for Pancreatic Cancer: Discovery, Tissue Validation, and Pilot Testing in Pancreatic Juice - Kisiel, John B. (Clin Cancer Res, 2015)
PURPOSE: Discriminant markers for pancreatic cancer detection are needed. We sought to identify and validate methylated DNA markers for pancreatic cancer using next-generation sequencing unbiased by known targets. EXPERIMENTAL DESIGN: At a referral center, we conducted four sequential case-control studies: discovery, technical validation, biological validation, and clinical piloting. Candidate markers were identified using variance inflated logistic regression on reduced-representation bisulfite DNA sequencing results from matched pancreatic cancers, benign pancreas, and normal colon tissues. Markers were validated technically on replicate discovery study DNA and biologically on independent, matched, blinded tissues by methylation specific PCR. Clinical testing of 6 methylation candidates and mutant KRAS was performed on secretin-stimulated pancreatic juice samples from 61 pancreatic cancer patients, 22 with chronic pancreatitis and 19 with normal pancreas on endoscopic ultrasound. Areas under receiver operating characteristics curves (AUC) for markers were calculated. RESULTS: Sequencing identified >500 differentially hyper-methylated regions. On independent tissues, AUC on 19 selected markers ranged between 0.73 – 0.97. Pancreatic juice AUC values for CD1D, KCNK12, CLEC11A, NDRG4, IKZF1, PKRCB and KRAS were 0.92*, 0.88, 0.85, 0.85, 0.84, 0.83 and 0.75, respectively, for pancreatic cancer compared to normal pancreas and 0.92*, 0.73, 0.76, 0.85*, 0.73, 0.77 and 0.62 for pancreatic cancer compared to chronic pancreatitis (*p=0.001 vs KRAS). CONCLUSION: We identified and validated novel DNA methylation markers strongly associated with pancreatic cancer. On pilot testing in pancreatic juice, best markers (especially CD1D) highly discriminated pancreatic cases from controls.